An intelligent rollator for mobility impaired persons, especially stroke patients. (3rd July 2016) - Hellström, Thomas; Lindahl, Olof; Bäcklund, Tomas; Karlsson, Marcus; Hohnloser, Peter; Bråndal, Anna; Hu, Xiaolei; Wester, Per
Abstract: An intelligent rollator (IRO) was developed that aims at obstacle detection and guidance to avoid collisions and accidental falls. The IRO is a retrofit four-wheeled rollator with an embedded computer, two solenoid brakes, rotation sensors on the wheels and IR-distance sensors. The value reported by each distance sensor was compared in the computer to a nominal distance. Deviations indicated a present obstacle and caused activation of one of the brakes in order to influence the direction of motion to avoid the obstacle. The IRO was tested by seven healthy subjects with simulated restricted and blurred sight and five stroke subjects on a standardised indoor track with obstacles. All tested subjects walked faster with intelligence deactivated. Three out of five stroke patients experienced more detected obstacles with intelligence activated. This suggests enhanced safety during walking with IRO. Further studies are required to explore the full value of the IRO.